(untitled) (REMUNOM, 2025)
The Caatinga is a biome characterized by semi-arid conditions and a diverse structure, harboring significant biodiversity with a high degree of endemism, containing factors that directly influence the composition of herpetofauna. Reptiles and amphibians perform essential ecological functions, acting as population controllers, seed dispersers, and environmental bioindicators, as well as acting as a fundamental link in food chains due to their sensitivity to microclimatic and structural changes in the habitat. However, the scarcity of studies on the use of microhabitats limits the understanding of their importance for the maintenance of biodiversity. This study aimed to investigate the species richness of herpetofauna associated with different microhabitats in the Camonga Mountains, in Santana do Ipanema (AL). Sampling was carried out between March and August 2025, covering dry and rainy periods, through active visual search, pitfall traps, and escape interception. Five main microhabitats were characterized: between rocks, under logs, dense shrubbery, exposed sandy soil, and accumulated leaf litter. In total, 20 species were recorded, including 8 amphibians and 12 reptiles, distributed among families such as Hylidae, Leptodactylidae, and Tropiduridae. The results indicate that the structural heterogeneity of the area supports specialists and generalists, reinforcing the relevance of Serra da Camonga as a refuge for regional biodiversity